Measurement of Project Cost and Time Efficiency with Earned Value Approach In The Implementation of Baggage Handling System at Sultan Hasanuddin International Airport Makassar - Digma Pratama, Irwansyah; Djoko Nugroho, Laksono; Muhammadun, Haris (Asian Journal of Social and Humanities, 2025)
The installation of the Baggage Handling System (BHS) at Sultan Hasanuddin International Airport, Makassar, faces challenges related to cost and time inefficiencies, particularly delays in project completion. This study aims to evaluate these inefficiencies by applying the Earned Value Method (EVM) to assess project performance and identify areas for improvement. Utilizing EVM metrics, the research identifies that the Schedule Performance Index (SPI) is below 1, indicating a delay in the project timeline, with the actual duration extending to 556 calendar days compared to the planned 546 days. This delay underscores the need for a more robust project management approach. The study employs the Critical Path Method (CPM) in conjunction with Microsoft Project to improve scheduling accuracy, alongside recommendations for project acceleration using the Crashing Program method. The findings highlight that early implementation of EVM can help mitigate discrepancies in cost and time, enabling better control and monitoring throughout the project lifecycle. The study concludes that integrating advanced scheduling techniques and real-time performance metrics is essential to achieving efficiency and minimizing delays in similar infrastructure projects.